Discovery of Guanidine Derivatives from Buthus martensii Karsch with Metal-Binding and Cholinesterase Inhibition Properties - Yu-Ming Liu (MDPI AG, 2021)
Two rare guanidine-type alkaloids, Buthutin A (1) and Buthutin B (2), along with two other compounds (3, 4), were isolated from Buthus martensii Karsch, and determined using extensive spectroscopic data analysis and high resolution-mass spectrometry. Compound 1 showed the most potent inhibition on AChE and BChE with IC50 values of 7.83 ± 0.06 and 47.44 ± 0.95 μM, respectively. Kinetic characterization of compound 1 confirmed a mixed-type of AChE inhibition mechanism in accordance with the docking results, which shows its interaction with both catalytic active (CAS) and peripheral anionic (PAS) sites. The specific binding of compound 1 to PAS domain of AChE was also confirmed experimentally. Moreover, compounds 1 and 3 exhibited satisfactory biometal binding abilities toward Cu2+, Fe2+, Zn2+ and Al3+ ions. These results provide a new evidence for further development and utilization of B. martensii in health and pharmaceutical products.